EXPANSION OF THE RANGE OF EMULSION-TYPE SAUCES BASED ON PRODUCTS OF SECONDARY PROCESSING OF MILK - Стукальська, Наталія; Винник, В.В. (SWorldJournal, 2024)
Emulsion sauces such as mayonnaise are a popular food product that is widely used in cooking. They are a dispersion of oil in water stabilized by egg yolk proteins.In recent years, milk-protein concentrate from shavings has increasingly been used for the